2011
DOI: 10.1097/mph.0b013e3181f46c22
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Infusion to Treat Severe Hypertriglyceridemia Associated With Pegaspargase Therapy

Abstract: We describe a pediatric patient with acute leukemia who developed an uncommon but significant metabolic consequence of pegaspargase therapy-severe hypertriglyceridemia (hyperTG). We also relate our experience with continuous insulin infusion treatment for pegaspargase-induced hyperTG. This treatment approach led to a decrease in triglycerides from 4640 mg/dL on admission to 522 mg/dL at discharge 9 days later. Genetic testing revealed that our patient was an apolipoprotein E 3/4 heterozygote. Our review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Occasionally, life-threatening emergencies have warranted plasmapheresis [15]. However, for asymptomatic patients or in those with milder symptoms, therapy has ranged from observation and dietary modification alone, [13] to steroid omission, [14] or pharmacotherapy with omega-3 fatty acids (FA), [16] fibrates, [12] statins, [17] heparin [12] or insulin [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, life-threatening emergencies have warranted plasmapheresis [15]. However, for asymptomatic patients or in those with milder symptoms, therapy has ranged from observation and dietary modification alone, [13] to steroid omission, [14] or pharmacotherapy with omega-3 fatty acids (FA), [16] fibrates, [12] statins, [17] heparin [12] or insulin [18]. …”
Section: Introductionmentioning
confidence: 99%
“…There are currently no standard treatment guidelines for asparaginaseinduced hypertriglyceridemia in pediatric patients with ALL. Isolated case reports and small reviews have suggested several approaches, namely short-term fasting or low-fat diet, oral fibrates, oral omega-3 fatty acids, and insulin infusion (7,10,12,13). Plasmapheresis has been shown to be effective in reducing TG levels rapidly after 2 h of apheresis (9); clinical improvement was seen as early as 8 h and normalization of the TG levels was achieved after 72 h of plasmapheresis (3).…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de las opciones dirigidas, se encuentra la administración de insulina (17), que promueve el almacenamiento de glucosa y de ácidos grasos, así como estimula comitante el HDL en cerca del 5 %. Por lo tanto, se infiere la pertinencia de la prescripción ambulatoria de estos ácidos en caso de que los fibratos se encuentren contraindicados) (30-32) (Tabla 5).…”
Section: Tratamientounclassified